Elements of Mental Health from the Viewpoint of the Quran and Hadiths - Aliahmad Naseh (Religious Inquiries, 2020)
Knowing the factors that secure mental health and using them in practice ensure peace of mind for the individual and society. The present study explores this topic in the Quran and hadiths. The study will show that, according to these two sources, the main factors in securing mental health for the individual and society are the following: enhanceing faith in God, trusting God, having a good opinion of God and positive thinking, being hopeful, maintaining the prayer, fasting, supplication, patience and perseverance, repentance, asceticism and restraint from vain worldly pleasures, love and affection, good-naturedness, marriage, and a decent profession.